2017
DOI: 10.1002/pola.28646
|View full text |Cite
|
Sign up to set email alerts
|

A versatile and rapid coating method via a combination of plasma polymerization and surface‐initiated SET‐LRP for the fabrication of low‐fouling surfaces

Abstract: In this work, we demonstrate the potential of surface-initiated single electron transfer living radical polymerization for surface modification applications that confer lowfouling properties. The versatility of the technique, which can be applied to a wide variety of substrates, has been displayed by the successful grafting of a range of monomers after immobilizing a bromine initiator on the surface via plasma polymerization. The thickness of the grafted surfaces can be controlled through variation of reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…1,5,26−29 In recent years it was shown that a range of hydrophilic PEG-based comb/brush polymers can be prepared fast and efficiently in mild conditions, including aqueous environment, by Cu(0)-mediated living radical polymerization. 30−37 For example, poly(methacrylates) were grown successfully on various surfaces to prevent nonspecific protein adsorption, 32,38 and graphene oxide (GO) was functionalized with poly(ethylene glycol) ethyl ether methacrylate (PEGEEMA) to improve GO dispersibility in various solvents and exhibit thermoresponsive wettability. 31 In this study we report the preparation and use of a macroinitiator obtained by site-specific covalent bioconjugation of a living radical polymerization initiator to the hydrophobin NCysHFBI.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,26−29 In recent years it was shown that a range of hydrophilic PEG-based comb/brush polymers can be prepared fast and efficiently in mild conditions, including aqueous environment, by Cu(0)-mediated living radical polymerization. 30−37 For example, poly(methacrylates) were grown successfully on various surfaces to prevent nonspecific protein adsorption, 32,38 and graphene oxide (GO) was functionalized with poly(ethylene glycol) ethyl ether methacrylate (PEGEEMA) to improve GO dispersibility in various solvents and exhibit thermoresponsive wettability. 31 In this study we report the preparation and use of a macroinitiator obtained by site-specific covalent bioconjugation of a living radical polymerization initiator to the hydrophobin NCysHFBI.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the materials possessing antifouling properties, poly­(ethylene glycol) (PEG) and its derivatives are well-known and have been studied and successfully employed over decades of research. ,, In recent years it was shown that a range of hydrophilic PEG-based comb/brush polymers can be prepared fast and efficiently in mild conditions, including aqueous environment, by Cu(0)-mediated living radical polymerization. For example, poly­(methacrylates) were grown successfully on various surfaces to prevent nonspecific protein adsorption, , and graphene oxide (GO) was functionalized with poly­(ethylene glycol) ethyl ether methacrylate (PEGEEMA) to improve GO dispersibility in various solvents and exhibit thermoresponsive wettability …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the versatility of this method has been shown recently through the synthesis of polymers in both aqueous and organic solvents, and through the fact that the catalyst can be recovered after the polymerization . In addition, this polymerization method can be combined with different methods including plasma polymerization to create novel classes of materials …”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric‐pressure plasmas have become a promising tool for surface modifications, particle deposition, and sterilization for medical tests lately. A vast number of applications require a large change in the surface energy or structural or chemical composition, for example, to enhance the wettability of a material …”
Section: Introductionmentioning
confidence: 99%